2021
DOI: 10.21638/spbu03.2021.207
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the barrier properties of the colon in rat

Abstract: The incidence of colorectal cancer in different parts of the large intestine is not the same, as tumors more often appear in the distal part of the colon compared to the proximal one. The purpose of this study was to investigate heterogeneity of the barrier properties of the colon and clarify the effects of Prostaglandin E2 and interleukin-1beta on its different parts. An in-depth analysis of short circuit current, transepithelial electrical resistance and paracellular permeability for sodium fluorescein in Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Previously, we conducted a segmental analysis of the barrier properties of the colon [ 63 ]. It was shown that the barrier properties were more pronounced in the proximal part of the colon compared to the distal part.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we conducted a segmental analysis of the barrier properties of the colon [ 63 ]. It was shown that the barrier properties were more pronounced in the proximal part of the colon compared to the distal part.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature, most studies of the barrier properties of the intestinal epithelium under cytokines action were carried out in vitro on cell cultures, with stimulation mainly from the basolateral side of the epithelium [ 37 , 64 , 65 ]. We stimulated the colon in situ from the apical side of the epithelium according to the approach we successfully used in our previous study [ 63 ]. We supposed that the addition of the cytokines to the mucosal side ensured their prolonged action and prevented their rapid enzymatic degradation by tissue cells.…”
Section: Discussionmentioning
confidence: 99%